Nexus between Remittances and Economic Growth in Nepal: An ARDL Bound Test Cointegration Approach - Adhikari, Dipa (Shiksha Shastra Saurabh, 2024)
This paper aims to investigate the nexus between remittances and economic growth in Nepal from 1993 to 2023, employing an Auto-Regressive Distributed Lag (ARDL) bound test cointegration model with time series data analysis techniques. The empirical findings reveal that both long-run and short-run coefficients indicate statistically significant and positively impact remittances on the Nepalese economic growth during the investigation period. This study's findings suggest that remittances play a pivotal role in improving living standards, economic development, and reducing poverty in Nepal. Moreover, this study found that government expenditures and labor variables have a positive influence on economic growth in the country. These results underscore the critical importance of remittances as a driver of sustainable development. The study results emphasize the need for targeted improvements in the management and effective utilization of remittances, positioning it as a strategic catalyst for promoting economic advancement in Nepal.